A framework of best practice by upstream oil and gas contractors in Malaysia / Muhammad Shafiq Hashim and Mohammad Fadhil Mohammad - Hashim, Muhammad Shafiq; Mohammad, Mohammad Fadhil (UiTM Press, 2024)
Due to unstable global economic conditions, Malaysia’s oil and gas industry encounters numerous challenges and uncertainties. Consequently, effective contract management has become a critical factor in ensuring the success of oil and gas projects. Projects undertaken by contractors are often exposed to various risks that can hinder project performance, cause financial instability, and lead to disputes, impacting all parties involved. Furthermore, many industrial practitioners overlook this issue and are unaware of the potential serious consequences. Hence, the primary objective of this study is to establish a theoretical framework for best practices in contract management for oil and gas contractors in Malaysia. A survey was conducted using questionnaires and a quantitative correlational research approach that employed a multistage cluster sampling method, targeting Malaysia’s oil and gas contractors. The study aimed to gauge the respondents' level of understanding and assess the effectiveness of their current contract management approaches. The collected data underwent analysis through descriptive methods, Pearson's correlation coefficient, and theoretical integration. The goal was to develop a novel framework comprising six core modules: staff accountability and Key Performance Indicators (KPIs), risk management, tender and award processes, cost management, contract awareness and review, and contractual recordkeeping. This framework equipped oil and gas contractors with the tools and practices necessary to navigate the global crisis. The oil and gas sector, particularly contractors, stands to gain substantial benefits from the framework introduced in this study. It is a valuable resource that contractors can leverage to enhance their methodologies, procedures, and contract management tools, enabling them to operate effectively amid the persisting global challenges.